Methods for control the self-sustained plasma-beam discharge at high energy density - Hrechko, Ya.O.; Azarenkov, N.A.; Tseluyko, A.F.; Ryabchikov, D.L.; Sereda, I.N. (Вопросы атомной науки и техники, 2019)
Three methods for control the self-sustained plasma-beam discharge at high energy density are presented in this paper. Using a particular method, it is possible to set the location of the double layers formation in the discharge gap, as well as control its parameters at the high-current inductive discharge stage. It is shown that such methods can significantly increase the active power inputted into the discharge. Наведено три методи керування самостійним плазмово-пучковим розрядом при високій густині енергії. Використовуючи певний метод, можна задавати розташування формування подвійних шарів у розрядному проміжку, а також керувати його параметрами на сильнострумовій індуктивній стадії розряду. Показано, що наведені методи дозволяють значно збільшити активну потужність, що вводиться в розряд. Приведены три метода управления самостоятельным плазменно-пучковым разрядом при высокой плотности энергии. Используя определенный метод, можно задавать местоположение формирования двойных слоев в разрядном промежутке, а также управлять его параметрами на сильноточной индуктивной стадии разряда. Показано, что приведенные методы позволяют значительно увеличить активную мощность, вводимую в разряд.